PENGARUH SUHU PEMADATAN TERHADAP STABILITAS DAN FLOW BAHAN LAPIS TIPIS ASPAL BETON (LATASTON) - , Marjono (Prokons: Jurnal Teknik Sipil, 2017)
In Indonesia, the highway pavement construction still use flexible pavement construction (Flexible Pavement). One of the problems often faced in the implementation time is to keep the temperature mix asphalt is still in the limit, This happens because it is associated with the weather conditions and the length of the transport of asphalt mixing point to the location. So often happens temperature asphalt mix location is at the lowest limit, and potentially non-fulfillment of the temperature required at this stage to stage compaction. This will result in the implementation of the road pavement quality and age will affect the service life of pavement construction. On the basis that the researchers took the title "The Effect of Temperature on the Stability and flow ?of Thin Layer Paving Asphalt Concrete ". The method used is the real experimental research is doing real research on the model Thin layers of asphalt pavement with concrete, size 100 cm wide, 300 cm long and thick Thin Layer Asphalt Concrete 5 cm. Treatment on the sample that is a variation solidification temperature (120 oC, 100 oC, 80 oC, 60 ?C) with 32 times the amount of compaction. The results showed that the solidification temperature affect the stability and flow value Thin Layer Asphalt Concrete, and the relationship between the solidification temperature on the stability of the equation written in the form y = -0,0315x2 + 10,155x - 349.33, where y = stability (Kg) and x = temperature (? C). and the relationship between the solidification temperature of the flow is written in the form of the equation y = -6E-05x2 + 0,0341x + 1.2935, where y = flow ?(mm) and x = temperature (? C)?Keywords: thin layer asphalt concrete, compaction temperature, pavement road